The Extended Exponential Weibull Distribution: Properties, Inference, and Applications to Real-Life Data. (23rd September 2022) - S. Mastor, Adam Braima; Ngesa, Oscar; Mung'atu, Joseph; Alfaer, Nada M.; Afify, Ahmed Z.
Abstract : A novel version of the exponential Weibull distribution known as the extended exponential Weibull (ExEW) distribution is developed and examined using the Lehmann alternative II (LAII) generating technique. The new distributions basic mathematical properties are derived. The maximum likelihood estimation (MLE) technique is used to estimate the unknown parameters of the proposed distribution. The estimators' performance is further assessed using the Monte Carlo simulation technique. Eventually, two real-world data sets are utilized to show the applicability of the new distribution.